Leadership Styles and their Impact on Innovativeness and Business Performance among SMMEs in Eastern Cape, South Africa - Mdingi, Cinga; Mapuranga, Miston (International Review of Management and Marketing, 2026)
This study investigates the influence of autocratic, democratic, transformational, and transactional leadership styles on business innovativeness and performance among Small, Medium, and Micro Enterprises (SMMEs) in the Eastern Cape Province of South Africa. A positivist quantitative methodology was employed, using a structured questionnaire to collect responses from 269 managerial-level employees within the SMME sector in Mthatha. Structural equation modelling (SEM) was used to validate the relationships between leadership styles, innovativeness, and business performance. The findings reveal that democratic, transformational, and transactional leadership styles significantly enhance business innovativeness, which in turn positively impacts business performance. Autocratic leadership, however, demonstrated a weak and statistically insignificant relationship with innovativeness. These results underscore the importance of participative and adaptive leadership in fostering innovation and improving performance in SMMEs. The implications suggest that policymakers and stakeholders should invest in leadership development and provide financial support to strengthen the competitiveness and scalability of emerging enterprises. This study contributes to the literature by extending leadership and innovation theory within the context of developing economies and offers practical insights for enhancing SMME sustainability.